International Choice of Law in Trademark Disputes From a Territorial Approach to a Global Approach - Treppoz, Edouard (The Columbia Journal of Law & the Arts, 2014)
It has been observed that international choice of law in trademark disputes reveals a tension between law and economics.1 From an economic perspective, marks can be exploited on a worldwide scale, and their value may be based on the global market. From a legal perspective, however, the rules are less than uniform. Law does not recognize one worldwide mark. Many trademarks are granted on a local basis, within local protective regimes that are independent of one another. Although the market has become global, the legal protection remains local. This tension has increased with the advent of the Internet. First, the universal access technology provides seems to reduce the relevance of a territorial approach and increase the need for a global economic approach. Second, the Internet has contributed to the creation of certain globally powerful companies. Those companies use, and benefit from, the universality of technology to make services available all over the world. From a technology-oriented point of view, the localized protection of trademark seems parochial. It is likely that the modern world requires a shift from local to international trademark protection.